A heideggerian hermeneutic study : Malaysian chinese women's expectations and experiences of childbirth - Lee, Na (Universiti Malaysia Sarawak, (UNIMAS), 2009)
Pregnancy and childbirth is considered as a turning point in women's life. Women have to adapt to the physiological and psychosocial changes. At the same time, they have to undergo the stress of childbirth as well. Women's experiences of childbirth can bring great impact on her life. Positive birth experiences can inspire their self confidence and bring about a sense of well being. Socio-cultural values, beliefs and health care system have significant influence on women's expectations and experiences of labour. Women's perception and coping manner, caregiver support, labour room management and obstetric interventions may vary from country to country. Thus, women's expectations and experiences of labour in Malaysia may vary from that in western cultures. As a result, the finding of the research studies conducted in the western cultures may be difficult to apply to Asian women. In view of the scarcity of phenomenological research conducted on women's childbirth experiences in Malaysia, it is timely to conduct this henneneutic phenomenological research to explore the lived experience of women undergoing childbirth. The philosophical framework that underpins the study is that of Heideggerian henneneutic phenomenology. Heideggerian henneneutic phenomenology is referred as the philosophy of interpreting the meaning of Being and reveal its significance. This study aims to understand and interpret women's childbirth experiences. To gain an in- depth ontological understanding of women lived experiences, it is necessary to obtain their narrative in order to capture the rich experiences vividly. Two sessions of in-depth interviews were conducted on eight criterion selected Chinese women. Women were asked to express their expectations on their childbirth as well as sharing the meaning embedded in their childbirth experiences. All interviews were recorded and transcribed verbatim. The informants' narrative on their lived experiences of childbirth was described under five major emergent themes. These themes were being apprehensive about childbirth, being enduring of the labour pain, being supported by the midwives, being compliance with the institutional rules and being thrown out of the crisis of childbirth. The five emergent themes were individually discussed in great depth from the Heideggerian perspective. The study highlights a number of issues in relation to obstetrical and midwifery practices. The issues that need to be addressed include the need to empower the women with sense of control, improve maternity services and strengthen autonomous midwifery practices. Cultural congruent maternity care should be considered in a multiethnic society like Malaysia.